Uso de ferramentas tecnológicas no ensino de física para o ensino médio: modelagem matemática a partir do software Modellus - Barsotti, Daniela Cristina (2014)
This work presents a case study on the teaching and learning of Physics concepts using mathematical modeling and technological tools, with software Modellus 4.01 as the main resource. Modellus 4.01 was selected due to its ability to provide a user-friendly platform for developing animated simulations from user-defined mathematical models, in addition to windows that can display graphs and tables dynamically. The main objective of this work is to propose an answer to the question: Is it worthwhile to use a computational tool with mathematical modeling to enhance student s learning results in secondary education? After all, much has been presumed about using computers to improve Brazil s overall performance in basic education, but there are very few formal studies on their actual utilization, especially at a complex level like the simulations from mathematical models developed by the students themselves. A sequence of activities for the modeling of kinematics concepts is proposed and discussed. While considering the steps of such sequence and their application with 9th-grade students in computer-equipped facilities, this work also presents and analyses the results of a diagnostic assessment of students theoretical knowledge; their acceptance of the Modellus software; the URM and UVRM simulations they developed; and the concepts they gathered from the work with modeling and computational tools. It is therefore possible to reflect upon the effectiveness of this methodology towards a more meaningful learning of the concepts involved, as well as the difficulties arising from the use of technological tools in the school environment. The outcomes from sharing the products and investigations of this work with other teachers, whether in specific projects like the Observatório da Educação (The Observatory of Education - Obeduc Capes-UFSCar) or in academic networking events are also discussed. In general terms, results show that the application of activities in the suggested order may be an important support to the motivation of students and to a meaningful learning of the Physics contents pertaining to the 9th grade program.